The godmother's web - Scarborough, Elizabeth Ann (New York : Ace Books, 1999)
This is the journey of sun-haired maiden Cindy Ellis. A path she thought would simply lead her to Tuba City to train a horse for a friend. But the old woman she has met along the way has asked for a ride on the blue horse. A ride that takes them to a world torn apart by poverty and sorrow. A world the old woman - the Godmother - watches over. And with her spindle in hand, she spins a web of love - so beautiful, so magical.
Keywords: Navajo women -- Fiction; Fantasy fiction